2021
DOI: 10.1017/s0025100320000377
|View full text |Cite
|
Sign up to set email alerts
|

Vowel quality in four Alemannic dialects and its influence on the respective varieties of Swiss Standard German

Abstract: Despite being one of the official languages in Switzerland, the phonetic properties of Swiss Standard German (SSG) have been studied insufficiently. Regarding Alemannic (ALM) dialects, most of the available phonetic studies have dealt with consonants rather than vowels. To counteract this general lack of research, this study investigates the long-vowel inventories of four ALM dialects as well as their respective SSG varieties regarding vowel quality. The aim of the study is twofold: on the one hand, it provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Region specificity of ALM and SSG vowel qualities as well as the way in which they interrelate were examined in Zihlmann's (2021) study. As for ALM, it was reported that GR high vowels tended to be pronounced less on the periphery compared to the other dialects.…”
Section: Vowel Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Region specificity of ALM and SSG vowel qualities as well as the way in which they interrelate were examined in Zihlmann's (2021) study. As for ALM, it was reported that GR high vowels tended to be pronounced less on the periphery compared to the other dialects.…”
Section: Vowel Qualitymentioning
confidence: 99%
“…Its realisation of /eː øː oː/ tended to be lower than elsewhere, while its /ɛː/, orthographically represented by <ä>, showed instances of being produced as either [eː], [ɛː], or [aeː] with much interspeaker variation observed. As the results are based on mean values per dialect region, it is unclear whether Zihlmann's (2021) insights are region-specific or speaker-specific, however.…”
Section: Vowel Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, we analyze data extracted from sociolinguistic interviews with 16 speakers from the city of Biel/Bienne that incorporated free conversation, two reading tasks, and a translation task (dialect to standard). In the analysis, we focus on the phoneticphonological variables /k/, /ç/, /aː/, and /ε-εː/, for which variation in spoken Swiss Standard German has already been amply demonstrated (e.g., Bülow, Büchler, Rawyler, Schneider, & Britain, 2021;Christen, Guntern, Hove, & Petkova, 2010;Hove, 2002;Siebenhaar, 1994;Zihlmann, 2021).…”
Section: Introductionmentioning
confidence: 99%